Nanoparticle distribution during systemic inflammation is size-dependent and organ-specific. Issue 38 (11th September 2015) - Chen, K.-H.; Lundy, D. J.; Toh, E. K.-W.; Chen, C.-H.; Shih, C.; Chen, P.; Chang, H.-C.; Lai, J. J.; Stayton, P. S.; Hoffman, A. S.; Hsieh, P. C.-H.
Abstract : This study comprehensively investigates the changing biodistribution of fluorescent-labelled polystyrene latex bead nanoparticles in a mouse model of inflammation. Abstract : This study comprehensively investigates the changing biodistribution of fluorescent-labelled polystyrene latex bead nanoparticles in a mouse model of inflammation. Since inflammation alters systemic circulatory properties, increases vessel permeability and modulates the immune system, we theorised that systemic inflammation would alter nanoparticle distribution within the body. This has implications for prospective nanocarrier-based therapies targeting inflammatory diseases. Low dose lipopolysaccharide (LPS), a bacterial endotoxin, was used to induce an inflammatory response, and 20 nm, 100 nm or 500 nm polystyrene nanoparticles were administered after 16 hours. HPLC analysis was used to accurately quantify nanoparticle retention by each vital organ, and tissue sections revealed the precise locations of nanoparticle deposition within key tissues. During inflammation, nanoparticles of all sizes redistributed, particularly to the marginal zones of the spleen. We found that LPS-induced inflammation induces splenic macrophage polarisation and alters leukocyte uptake of nanoparticles, with size-dependent effects. In addition, spleen vasculature becomes significantly more permeable following LPS treatment. We conclude that systemic inflammation affects nanoparticle distribution by multiple mechanisms, in a size dependent manner.